Durovigutum Roman Godmanchester - Green, H. J. M. (Henry James Michael), 1931- (Archaeopress Roman archaeology ;, 2018)
This publication presents the results of over 30 years of investigation into Roman Godmanchester, (Cambridgeshire), by Michael Green. The book accurately locates the 25 'sites' investigated, and pinpoints the trenches against the modern street layout. Although some sites covered large areas, many often had to be conducted as small trenches undertaken by volunteers. The origins for Durovigutum include evidence for Iron Age settlement which preceded two Roman forts during the 1st century AD.